A Semantics for Web Services Authentication - Bhargavan, Karthik; Fournet, Cédric; Gordon, Andy (Association for Computing Machinery, Inc., 2004)
We consider the problem of specifying and verifying cryptographic security protocols for XML web services. The security specification WS-Security describes a range of XML security elements, such as username tokens, public-key certificates, and digital signatures, amounting to a flexible vocabulary for expressing protocols. To describe the syntax of these elements, we extend the usual XML data model with symbolic representations of cryptographic values. We use predicates on this data model to describe the semantics of security elements and of sample protocols distributed with the Microsoft WSE implementation of WS-Security. By embedding our data model within Abadi and Fournet's applied pi calculus, we formulate and prove security properties with respect to the standard Dolev–Yao threat model. Moreover, we informally discuss issues not addressed by the formal model. To the best of our knowledge, this is the first approach to the specification and verification of security protocols based on a faithful account of the XML wire format.
Proceedings of Tenth Conference on Uncertainty in Artificial Intelligence, Seattle, WA